Analisis Pengaruh Intensitas Radiasi Matahari Terhadap Tegangan Dan Arus Pada Panel Surya Di Universitas Negeri Manado - Jutisya Putrih Senaen; Alfrie Rampengan; Farly Tumimomor (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
The Solar Power Plant (PLTS) represents one of the pioneering electricity producers established at Manado State University. The aforementioned solar cell technology is a mechanism that effectively transforms solar energy into electrical energy. Indonesia, being situated on the equator and endowed with ample sun resources, stands to benefit significantly from the adoption of solar energy, thus enhancing its effectiveness. This study employs a quantitative methodology with a descriptive framework to examine the impact of light intensity on the voltage and current of solar panels. Based on the obtained measurements, it can be observed that the intensity of the sun is directly proportional to its brightness, assuming that there is no cloud cover. In ideal bright conditions, the maximum duration for the absorption of solar energy in a single day can extend up to 9 hours. On the contrary, the duration of optimal absorption during overcast or rainy weather conditions is limited to a maximum of five hours during a single day. The calculations were conducted using the average power generated on the initial day, which amounted to 30,299.76 kilowatt-hours per day, and on the subsequent day, which totaled 40,991.22 kilowatt-hours per day. There exists a positive correlation between the intensity of solar radiation and the performance of solar panels, whereby an increase in intensity leads to a corresponding increase in panel performance.